Exploring Environmental Sustainability Attitudes among students pursuing Ayush course in India: A Cross-Sectional Study - Dr. Farha Rizwan Sikalgar; Dr Manasvi P Kumar; Sarene Thomas; Dr Deepak Bangera; Dr Shrikanth Muralidharan (The Bioscan, 2024)
Background: Despite its low per-capita emissions, the country ranks as the third-largest global greenhouse gas emitter. The healthcare sector, specifically alternative medicine, which derives its basis from natural products such as plants and earth, can potentially drive transformative change in sustainability practices. Method: Through an online survey, this study investigates the attitudes of interns pursuing complementary and alternative medicine towards environmental sustainability (ES). Ethical clearance was secured, and a meticulously reviewed questionnaire was disseminated among 540 participants using a non-linear snowball sampling technique. Data analysis included statistical tests to explore perceptions, engagement levels, and priorities regarding ES. The study reveals a predominantly young demographic with a strong inclination towards ES, highlighting its ethical significance. Results: Notably, 68.52% of respondents believed an environmentally sustainable healthcare campus should include reduced plastic usage, green spaces, and proactive water conservation efforts. Additionally, a significant majority, 87.04%, acknowledged the potential for financial benefits through ES practices. More than 90% of respondents indicated that less than 20% of their staff were involved in ES-related research (p=0.04). The significance of incorporating ES into the academic curriculum received resounding support, with 97.22% of participants advocating for its inclusion (p<0.01). Conclusion: Interns in India strongly support environmental sustainability in healthcare. However, converting this support into effective policy change necessitates concerted efforts, including educational reforms, interdisciplinary collaborations, and active advocacy. Addressing climate change and ensuring a sustainable healthcare future is paramount, and Ayush stands as a potent catalyst for positive change in India's journey towards a sustainable healthcare system.